Assessment of the suitability of blood samples collected for toxicological analysis for subsequent genetic analysis: A follow-up study one year later - Musiyandaka, Fungisai Lorraine (Department of Pathology, 2020)
Drug usage, both of a recreational or pharmaceutical nature, is common, however the abuse of such substances is an international problem. In the Western cape, South Africa, the burden of drug-related fatalities is high compared to the rest of the country. The provincial Forensic Pathology Service may encounter cases where drug-related fatalities are unclear whether death was accidental or suicidal, or drug toxicity is inconsistent with the medical/social history. This may be due to genetic alterations with drug metabolism and it has been suggested that genetic analyses may be the next step in these cases. However, toxicology results from the National Forensic Chemistry Laboratory in the Western Cape may be delayed by months to years, meaning that upon interpretation of toxicology results, there is no chance to obtain another blood sample from the deceased individual for genetic analysis. It was therefore important to determine the suitability of blood samples collected and handled in toxicology environments for subsequent genetic tests. Previously, blood samples from 30 post-mortem cases were collected into two red-top (no additives), two grey-top (sodium fluoride/potassium oxalate) and one purple-top (EDTA) tubes. Samples from one red-top and one grey-top tube underwent toxicological analysis, followed by DNA analysis, while the remaining tubes (controls) underwent DNA analysis immediately. All samples were then stored for approximately one year, prior to this study. The DNA analysis was repeated on all blood samples (n = 150) and results were assessed in terms of storage time and tube type. DNA was not significantly degraded in any of the samples; however, DNA from red-top tubes had significantly lower concentrations compared to that from grey-top tubes (p < 0.001), regardless of whether the sample had undergone toxicological analysis. The very low yields of DNA from red-top tubes posed substantial challenges for PCR-based analysis, resulting in poor quality Sanger sequencing results. Some DNA from grey-top tubes, passed the quality assessments and hence further work is required to provide an informed decision on which tube type is better suited for genetic analyses.